National treasure 2 : book of secrets - Turteltaub, Jon; Cage, Nicolas, 1965-; Voight, Jon, 1938-; Bartha, Justin (Burbank, CA : Walt Disney Home Entertainment, 2008)
Benjamin Franklin Gates is looking for a book containing centuries of secrets and must take several actions to recover it, including kidnapping the President of the United States.
Originally released as a motion picture in 2007.
Sequel to the film "National treasure" (2004).
Features: audio commentary with director Jon Turteltaub and actor Jon Voight, deleted scenes, bloopers and outtakes, "Secrets of a sequel," "The book of secrets : on location," "Street stunts : creating the London chase," "Inside the Library of Congress," "Underground action," "Cover story : crafting the President's book," "Evolution of a golden city," "Knights of the Golden Circle."
Nicolas Cage, Jon Voight, Justin Bartha, Diane Kruger, Helen Mirren, Ed Harris.
MPAA rating: PG.
DVDs, Dolby digital 5.1 surround.
Keywords: Lost articles -- Drama; Treasure troves -- Drama; Adventure films; Thrillers (Motion pictures, television, etc.); Film sequels; Fiction films; Feature films